Building teacher competency in the 21st century: a comparative study of selected secondary schools in three developing countries - Preece, Abdul Shakour Duncan; Hamed, Popoola Kareem; Juperi, Juhasni Adila (NAMA Foundation, 2024)
This paper presents the findings of a comparative study conducted in selected secondary schools across three developing countries, Tanzania, Kyrgyzstan and Indonesia that focused on building teacher competency for the 21st century. The study aimed at enhancing teaching and learning by empowering teachers, toward advancing human capital in the educational landscape of three developing nations. The study employed a mixed-method approach combining classroom observation and surveys to evaluate teachers' performance, following the implementation of the NAMA Foundation ROOTS programme. The evaluation was based on the NAMA Theory of Change (ToC) Index Indicators, focusing on 'Learning Success-Teachers' (LST) and 'School Culture and Values-Teachers' (CVT). The findings indicate a positive impact on teachers' competency in the key indicator LST 1, and their sense of efficacy in key indicator CVT 1, with increases of 1.0 and 0.9 respectively. These results suggest significant advancement in teaching competency across the selected schools of the three nations. However, further improvements are anticipated in the areas of 'pedagogy & assessment' key indicator LST 2, and teachers' willingness to learn from peers, key indicator LST 3. Improving education in Tanzania, Kyrgyzstan, and Indonesia requires tailored strategies that address local challenges while leveraging opportunities for innovation and inclusivity. Effective implementation of these strategies demands collaboration among governments, educators, communities, and international partners to ensure sustainable improvements in educational outcomes and socio-economic development